2019
DOI: 10.1108/emjb-11-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and the cities in a knowledge-based perspective: evidences from EU

Abstract: Purpose The purpose of this paper is to answer the following research questions: Is the knowledge of a city environment a stimulus for entrepreneurship? Which knowledge profiles of cities are more propulsive in order to stimulate entrepreneurship? Design/methodology/approach In order to answer the aforementioned research questions, two multidimensional indexes have been created: Knowledge-Based City Developing Entrepreneurship and Entrepreneurship (ENT). The sample includes all capital cities in the EU28. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Studies have observed that knowledge management activities help different firms to improve their innovation with effective marketing management technique (Boso et al , 2013; Karagouni et al , 2018; Tsai and Shih, 2004). Although MKM has ample opportunities, even in the international marketing arena, to sustain competitive advantage, studies of this aspect are found to be at a rudimentary stage (Cadogan, 2012; Penco et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have observed that knowledge management activities help different firms to improve their innovation with effective marketing management technique (Boso et al , 2013; Karagouni et al , 2018; Tsai and Shih, 2004). Although MKM has ample opportunities, even in the international marketing arena, to sustain competitive advantage, studies of this aspect are found to be at a rudimentary stage (Cadogan, 2012; Penco et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, this unrivaled situation poses a significant challenge to the safety of health-care workers who face a major risk of getting infected while providing care for confirmed or suspected Covid-19 cases. This horrific situation compels health-care workers to develop innovative ways to protect themselves, especially when innovation strategies of knowledge are also sources of competitive advantage for health-care institutions (Penco et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To spread information through IM is easy, thus helping people to exaggerate news about a crime (Augner and Hacker, 2012). Such exaggerated news on IM platform causes offences such as mob lynching (Bandura, 1997; Garret and Danziger, 2008; Gupta et al , 2018a; Penco et al , 2019). Moreover, spreading information through this electronic means is inexpensive, which influences people to use it (Hamari et al , 2015; Kim and Shin, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%